1994
DOI: 10.1182/blood.v84.7.2130.bloodjournal8472130
|View full text |Cite
|
Sign up to set email alerts
|

Passive hyperimmune plasma therapy in the treatment of acquired immunodeficiency syndrome: results of a 12-month multicenter double- blind controlled trial. The Passive Hyperimmune Therapy Study Group [see comments]

Abstract: High-titer anti-human immunodeficiency virus (HIV) antibodies reduced circulating HIV viral burden and has shown promise in previous small uncontrolled studies, warranting a larger controlled study of passive hyperimmune therapy (PHT) in persons with acquired immunodeficiency syndrome (AIDS). The objective of this study was to determine the efficacy and safety of PHT in 220 AIDS subjects in a 12-month double- blind placebo-controlled dosing study. Subjects were randomized to receive monthly infusions of 500 mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…A short-term study on PIT in AIDS patients in the USA recorded HIV neutralisation and a reduced frequency of opportunistic infections ( Jackson et al, 1988). Thereafter two independent larger-scale, double-blind, placebo-controlled trials of PIT in patients with advanced disease were conducted in the USA (Levy, Youvan & Lee, 1994) and France (Vittecoq et al, 1995). The USA trial concentrated on mortality and found improvement in the group of patients with a CD4+ T-cell count exceeding 50 mm x3 .…”
Section: (10 ) Passive Immunotherapy (Pit)mentioning
confidence: 99%
See 1 more Smart Citation
“…A short-term study on PIT in AIDS patients in the USA recorded HIV neutralisation and a reduced frequency of opportunistic infections ( Jackson et al, 1988). Thereafter two independent larger-scale, double-blind, placebo-controlled trials of PIT in patients with advanced disease were conducted in the USA (Levy, Youvan & Lee, 1994) and France (Vittecoq et al, 1995). The USA trial concentrated on mortality and found improvement in the group of patients with a CD4+ T-cell count exceeding 50 mm x3 .…”
Section: (10 ) Passive Immunotherapy (Pit)mentioning
confidence: 99%
“…There is evidence that the effects of PIT are dose-related : when AIDS patients received only 250 ml of plasma on a monthly basis there was no benefit ( Jacobson et al, 1993;Levy et al, 1994 ;Vittecoq et al, 1995). For patients with advanced disease, 500 ml of plasma per month is probably the minimum requirement.…”
Section: (10 ) Passive Immunotherapy (Pit)mentioning
confidence: 99%
“…Autologous and heterologous neutralizing antibodies are detected more frequently in mothers who do not transmit virus, indicating that their presence can prevent vertical transmission, although a recent study could not find a protective role for maternal neutralizing antibodies [Scarlatti et al, 1993;Hengel et al, 1998]. Passive administration of antibodies to HIV-infected patients is associated with reduced p24 antigen levels or increased CD4 + T-lymphocyte cell counts [Jackson et al, 1988;Karpas et al, 1988;Vittecoq et al, 1992;Levy et al, 1994]. A combination of human monoclonal antibodies (Mabs) targeting different HIV-1 envelope glycoprotein epitopes exhibits a strong synergic neutralization capacity against a chimeric simian-human immunodeficiency virus [Li et al, 1998].…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to characterize this protective component in the light of the data of the present study, but one can make assumptions about some of its characteristics: this component is present in the plasma, may be passively administered through transfusion and resists heating (plasmas infused were heated at 56 C for 30 min to inactivate HIV). The clinical differences observed between the previously published PI trials based on infusions of HIV-positive plasma every 4 weeks [4,12] and the trials with infusions every 2 weeks [5] suggest that this protective component has a lifespan markedly inferior to 1 month. This component acting on the immune system is not the heat-inactivated soluble factor produced by the CD8 lymphocytes and able to control HIV replication in infected CD4 lymphocytes [13].…”
Section: Discussionmentioning
confidence: 82%